The psychology of extreme violence: a case study approach to serial homicide, mass shooting, school shooting and lone-actor terrorism - Allely, Clare S. (Routledge, Taylor & Francis Group, 2020)
Featuring a unique overview of the different forms of extreme violence, this book considers the psychology of extreme violence alongside a variety of contributing factors, such as brain abnormalities in homicide offenders. Featuring several contemporary real-world case studies, this book offers insight into the psychology of serial homicide offenders, mass shooters, school shooters and lone-actor terrorists. The main purpose of this book is not to glorify or condemn the actions of these individuals, but to attempt to explain the motivations and circumstances that inspire such acts of extreme violence. By adopting a detailed case study approach, it aims to increase our understanding of the specific motivations and psychological factors underlying extreme violence.